Xerogel of fast kinetics and high adsorption capacity for cationic dye removal - Sezgin, Deniz; Yilmaz, Muge Sari (YILDIZ TECHNICAL UNIV, 2024)
Silica-based xerogel was prepared by the two-step sol-gel method to investigate its methylene blue removal performance. The characteristics of the prepared adsorbent were determined using X-ray diffraction (XRD), Fourier transforms infrared (FTIR), scanning electron microscopy (SEM), and N2 adsorption/desorption analyses. The MB removal studies were conducted with different operating parameters and optimal conditions were found to be 0.06 g adsorbent dosage, and 20 mg.L-1 initial MB concentration at 45 min. The Langmuir isotherm best represents the MB adsorption equilibrium data and the high maximum adsorption capacity was achieved with 1666.67 mg.g-1. The kinetic mechanism of the study is defined by the pseudo-second-order kinetic model. Additionally, the adsorption of MB on xerogel exhibited fast kinetics, reaching a high removal capacity (96.56%) in a minute.
Keywords: Xerogel; Fast Kinetics; High Capacity; Adsorption; Cationic Dye; METHYLENE-BLUE ADSORPTION; AQUEOUS-SOLUTION; SILICA NANOPARTICLES; ACTIVATED CARBON; HYBRID ADSORBENT; WASTE; EQUILIBRIUM; PERFORMANCE; MECHANISM; ALGINATE; Engineering